Zoning of wastewater quality fluctuations in the Birjand city collection network - Hooman Bahmanpour; Farkhondeh Ahrari (آلودگی‌های محیطی و توسعه پایدار شهری)
This research aimed to investigate the quality status of the Birjand city wastewater network and develop a zoning model. Over three sampling periods, 10 quality parameters were measured at 19 points within the urban wastewater network. Following statistical analysis, variogram analysis was conducted using GS+ software to facilitate interpolation methods. Appropriate zoning was then performed using the Cross Validation method with ArcGIS 10.1 software and the Geo-statistical analyst toolbox. To determine the most suitable estimation method, sensitivity analysis was conducted using two statistical approaches. Correlation analysis was performed using the Spearman method, which consistently demonstrated the superiority of the Bayesian Kriging method in zoning accuracy over other methods. The zoning results obtained through Bayesian Kriging indicated high BOD and COD concentrations in the northern region of the city, along with elevated EC levels, increased nitrate, decreased nitrite, and high TDS and pH at the endpoint of the sewage network. The presence of high BOD and COD concentrations suggests slow organic matter decomposition. To accelerate biological decomposition, implementing management solutions, particularly hydraulic system improvements in the sewage network of Birjand, is crucial to initiating the treatment process earlier.